Histopathological Examination of Uterine Evacuation Products Following First Trimester Abortion Along with Clinico-Pathological Correlation in A Tertiary Care Centre: A Descriptive Study - Shah, Dhruvi; Sinha, Riti T.K (Annals of Pathology and Laboratory Medicine, 2019)
Background: Spontaneous abortion also known as miscarriage is one of the most common conditions encountered by the gynecologists and obstetricians. The women who had spontaneous miscarriage have traditionally undergone surgical uterine evacuation of retained products of conception. In recent years more and more patients are evaluated with more and more refined diagnostic techniques and therapeutic interventions. In our center too, it is a routine practice to submit tissues obtained by uterine evacuation to the histopathology department, and to confirm intrauterine fetal tissue. Methods: The present retrospective study was done for a period of one year in the department of Pathology, Gujarat Adani institute of medical sciences, G. K General Hospital, Bhuj. Total 62 samples of uterine evacuation products were evaluated. Along with their clinico-pathological correlation the histopathological spectrum of the lesions were also studied and the necessary statistical analysis was done. Result: The most common clinical diagnosis was retained product of conception (34%), followed by hydatidiform mole (24%). The most common histological finding was presence of chorionic villi (55%), followed by presence hydatidiform mole (24%). Clinico-pathological correlation was found in (79%). Conclusion: The present study was to highlight the importance of histopathological evaluation of the uterine evacuation products. Our study strongly recommends the histopathological examination of all uterine evacuation products as it aids in timely management of the patients.